IMPROVING THE MECHANISMS OF ORGANIZATION OF PEDAGOGICAL PROCESSES IN GENERAL SECONDARY EDUCATIONAL INSTITUTIONS - Turakhodjaeva Zulhumor Yusufjanovna (American Journals, 2022)
Modern society sets before the school the tasks of becoming an individual person capable of independently solving the tasks assigned to him; having a high level of professional training; for the formation of a person and a citizen who is a conscious member of modern society, focused on the progressive development and improvement of this society. Modern education should develop students' creative abilities, enrich the spiritual and moral development of the individual. Thus, modern society today does not need a standard personality, but an individuality.
Keywords: Modern education, general secondary educational institutions, education quality, pedagogical process